Biological iron-sulfur storage in a thioferrate-protein nanoparticle - Brian J. Vaccaro; Sonya M. Clarkson; James F. Holden; Dong-Woo Lee; Chang-Hao Wu; Farris L. Poole II; Julien J. H. Cotelesage; Mark J. Hackett; Sahel Mohebbi; Jingchuan Sun; Huilin Li; Michael K. Johnson; et al. (Nature Communications, 2017)
The biosynthesis of iron-sulfur clusters in anaerobic organisms has not been extensively investigated. Here, the authors identify and characterize a multi-subunit protein that stores iron and sulfur in thioferrate for the assembly of the clusters inPyrococcus furiosus.